Asthmatic Bronchial Matrices Determine the Gene Expression and Behavior of Smooth Muscle Cells in a 3D Culture Model - Ben Hamouda, Selma; Miglino, Maria Angélica; de Sá Schiavo Matias, Gustavo; Beauchamp, Guy; Lavoie, Jean-Pierre (Frontiers in Allergy, 2021)
Asthma is associated with an increased deposition and an altered phenotype of the airway smooth muscle (ASM) cells. However, little is known of the processes responsible for these changes. It has been suggested that alterations of the extracellular matrix (ECM) contribute to the remodeling of the ASM cells in asthma. Three-dimensional matrices allow the in vitro study of complex cellular responses to different stimuli in a close-to-natural environment. Thus, we investigated the ultrastructural and genic variations of ASM cells cultured on acellular asthmatic and control bronchial matrices. We studied horses as they spontaneously develop a human asthma-like condition (heaves) with similarities to the chronic pulmonary changes observed in human asthma. Primary bronchial ASM cells from asthmatic (n=3) and control horses (n=3) were cultured on decellularized bronchi from control (n = 3) and asthmatic (n = 3) horses. Each cell lineage was used to recellularize the 6 different bronchi for 41 days. Histomorphometry on HEPS-stained-recellularized matrices revealed an increased ASM cell number in control cells/control matrices (p = 0.02) and asthmatic cells/control matrices groups (p = 0.04) compared to asthmatic cells /asthmatic matrices group. Scan electron microscopy revealed a cell invasion of ECM. While ASM cells showed high adhesion and proliferation processes on control ECM, the presence of senescent cells and cellular debris in asthmatic ECM with control or asthmatic ASM cells suggested cell death. When comparing asthmatic to control cell/matrix combinations using targeted next generation sequencing, only AGC1 (p = 0.04), MYO10 (p = 0.009), JAM3 (p = 0.02) and TAGLN (p = 0.001) were differentially expressed out of a 70 genes pool previously associated with smooth muscle remodeling. To our knowledge, this is a first attempt to evaluate the effects of asthmatic ECM on ASM cells phenotype using a biological bronchial matrix. Our results indicate that bronchial ECM health status contributes to ASM cell gene expression and possibly, its survival.